Stress-Induced Mutagenesis - Mittelman, David; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The discoveries of stress-induced mutation and epigenetic inheritance have challenged the claim of independence between the evolutionary forces of mutation and selection. In (3z(BStress-Induced Mutagenesis(3y(B, leading experts provide the key evidence for and the molecular details of stress-induced genetic and epigenetic mutation, integrating cross-disciplinary observations from a number of species and biological systems, including human. The observations have vast implications for evolutionary biology but also for human medicine. A comprehensive understanding of stress-induced mutagenesis and the processes underlying evolvability, will enable gains in the treatment and management of cancer, as well as other human disorders that result from damaged or unstable genomes.s
Preface -- Stress-induced mutagenesis in bacteria -- Mutagenesis Associated with Repair of DNA Double-Strand Breaks Under Stress -- Transcription-mediated mutagenic processes -- Transposon mutagenesis in disease, drug discovery and bacterial evolution -- Hsp90 as a capacitor of both genetic and epigenetic changes in the genome during cancer progression and evolution -- Inheritance of stress-induced epigenetic changes mediated by the ATF-2 family of transcription factors -- Microsatellite Repeats: Canaries in the Coalmine -- Genetic instability Induced by hypoxic stress -- Radiation-induced delayed genome Instability and hypermutation in mammalian cells -- Radiation-induced bystander effects and stress-induced mutagenesis -- Stress induced mutagenesis, genetic diversification, and cell survival via anastasis, the reversal of late stage apoptosis -- The transgenerational effects of parental exposure to mutagens in mammals -- Revisiting mutagenesis in the age of high-throughput sequencing -- Index.
Keywords: Medicine; Human genetics; Biochemistry; Biomedicine; Human Genetics; Biochemistry, general; Biomedicine general